Ad occhi chiusi. Il sistema delle Rems di fronte alla Corte costituzionale (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The transition from the old model of the Judicial Psychiatric Hospitals to the reformed system of the Rems (territorial residences for the execution of detention security measures) has produced an imbalance between the demand and the availability of places in these facilities, thus creating the phenomenon of so-called waiting lists. This phenomenon has been the subject of a referring order to the Constitutional Court challenging the provision which excludes the Justice Department from the implementation of the security measures. The paper critically analyses the arguments at the base of the order and evaluates the possibility of dealing with the request for the implementation of custodial security measures, as required by Law n. 81/2014, through a continuous work to improve the network that involves the judiciary and mental health services.
Keywords: Detention; security measures; detention facilities; law 81/2014; constitutional law